Testimony and Narrative of Pahadi’s “The Tears of Terror” - Pokharel, Badri Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper makes an attempt to analyze trauma and testimony in Kishor Pahadi’s “The Tears of Terror” by applying cultural trauma perspectives. The story has brought some painful experiences of a conflict victim during the ten years Maoist conflict that took the lives of more than seventeen thousand innocent people. This article aims to bring the facts about conflicts and wars which have always brought destruction in human life, and later pain and suffering for those who survived the disaster, but such catastrophes can have a creative dimension upon the victims who have witnessed the events. These painful memories in the form of testimony can be a source for writing narratives which can help one understand history and many hidden facts – emotional attachments of the victims and of the perpetrators, that happened quite long ago. Wars fought in past have been talked about and brought out in narratives for a long time. Narrativizing the past conflict as it was has been considered an important task for writers. Bearing witness to such events and presenting them as testimony has become a crucial task for many literary works.